TYPES OF SURGERIES PERFORMED AT NECK WOUNDS IN CIVIL MEDICAL INSTITUTION IN THE CONDITIONS OF THE LOCAL MILITARY CONFLICT - V. V. Maslyakov; V. G. Barsukov; A. V. Uskov (Исследования и практика в медицине)
Objectives. To make analysis of main types of surgeries performed at various neck wounds in civil medical institution in the conditions of the local military conflict.Patients and methods. The work is based on a retrospective analysis of the treatment of 241 patients with various neck wounds who were admitted in an urgent order to the surgical department of a city hospital in Chechen Republic from 1991 to 2000. All the wounded were divided into two groups: 129 with gunshot wounds (main group) and 112 with stab wounds of the neck (comparison group). The average age was 35 ± 5 years, dominated by males — 78%.Results. It was established that in 25 (19.3%) cases the operation was started under local anesthesia, in 45% of cases anesthesia was given to continue the surgery, in 84% intubation was made, in 16% — intravenous operations. As a result of the analysis, it was revealed that for neck gunshot wounds the following operations were most often performed: a typical tracheostomy without a laryngeal and tracheal suture in 26.3% cases; atypical tracheostomy without suture of larynx and trachea — 16.2% cases; the laryngeal or tracheal suture with tracheostomy was performed in 13.1% cases, in 12.4% of cases was performed operative exploration of neck organs.In cases of concomitant chest wounds, in 10.8% of cases, in addition to operative exploration of neck organs, thoracotomy was performed, in most cases for suturing wounds of the esophagus.Conclusion. The study confirmed that in the wounded with neck gunshot wounds, the amount of aid consisted primarily in restoring airway patency, stopping bleeding and anti-shock actions.